PELATIHAN LITERASI MEMBACA TEKS DESKRIPTIF MELALUI IMPLEMENTASI STRATEGI POWER NOTES PADA SISWA SMP YABES SCHOOL - Juliana Juliana; Enni Maisaroh; Dela Mitha (LPPM Universitas Nusa Mandiri, 2026)
This community service program aimed to improve students’ reading literacy through training in the Power Notes strategy for descriptive texts at SMP Yabes School. The program was designed to provide an active, structured, and practical learning experience in understanding English texts. The main problem addressed was students’ limited ability to identify main ideas, find supporting details, recognize specific information, and understand descriptive texts comprehensively. The activity employed a participatory training and mentoring approach consisting of preliminary observation, material development, strategy training, guided practice, evaluation, and reflection. The participants were 30 eighth-grade students of SMP Yabes School. Data were collected through observation, pre-test and post-test, student worksheets, and participant response questionnaires. The findings indicate that students’ reading literacy improved after the training. The score for identifying main ideas increased from 60 to 85, finding supporting details from 58 to 82, identifying specific information from 55 to 80, and overall text comprehension from 57 to 84. Students also gave positive responses, with an agreement level of 80%–85%, reflecting higher motivation, engagement, and confidence in learning English. The program produced a Power Notes training module, student worksheets, and measurable improvement in students’ reading literacy skills. These results suggest that the Power Notes strategy is effective in supporting reading literacy training and can be applied as an innovative instructional strategy in school-based community service programs.